DESCRIPTIVE BOOK REVIEW OF UNDERSTANDING HUMAN NATURE: THE PSYCHOLOGY OF PERSONALITY BY ALFRED ADLER - Yushini Hasya Nuha; Yusi Riska Yustiana (Universitas Pendidikan Mandalika, 2026)
Humans are moving and rational beings who can choose their actions and adapt to the challenges of life. This book explains how everyday behavior can influence social harmony and communication, teaching readers to accept mistakes and adapt. The purpose of this book review is to present Alfred Adler's main ideas on human personality. The method used is a descriptive review approach. This book explains a better understanding of human nature.